Bridging performances of lost circulation materials (LC-LUBE and mica) and their blending in 80/20 and 60/40 oil-based drilling fluids - Belayneh, Mesfin; Aadnøy, Bernt (Frontiers in Physics, 2022)
In drilling wells, loss circulation, barite sagging, and shale swelling are critical problems for the industry. These problems can be controlled by designing appropriate drilling fluids. In this paper, the performance of 80/20 and 60/40 oil-based drilling fluids (OBM) are compared. The analysis was based on bridging performance, filtrate loss, barite sagging shale stability. Results show that: • In terms of particle stability, the performance of LC-lube is improved when blended with Mica. • In terms of shale stability, both drilling fluids inhibit equally the shale swelling and disintegration. • In terms of barite sagging, filtrate loss and bridging performances, the 60/40 is better and recommended.